Tinjauan Pastoral terhadap Aspek Komunikasi dalam Penatalayanan Gereja - Sihombing, Salomo (Sekolah Tinggi Diakones HKBP, 2022)
The communication pattern in church stewarship should be a constructive communication based on the awareness that differences and similarities are realities that God’s love can glue together. Church stewards should be aware that they are people who carry out the task of stewardship from God, the Church Owner.